Sellar B lymphoblastic lymphoma mimics pituitary apoplexy with newly discovered gene mutations in TP53 and PAX5: A case report - Wang, Yi; Yang, Yajun; Wang, Qiuxia; Wang, Ce; Xu, Xinjuan; Wang, Dongao; Bai, Feirong; Li, Panpan; Huang, Xintao (Frontiers in Oncology, 2023)
Lymphoblastic lymphoma (LBL) is a rare tumor that accounts for approximately 2-4% of all non-Hodgkin lymphomas, and less than 20% of LBLs are derived from B cells. B- Lymphoblastic lymphoma (B-LBL) often presents as bone marrow and peripheral blood lesions, and is very rare to present as a seller mass. We report a case of sellar B lymphoblastic lymphoma mimicking pituitary apoplexy, and review its diagnosis and treatment process, combined with the literature to deepen the understanding of sellar tumors.